Prevalence and socio-demographic correlates of the compliance with the physical activity guidelines in children and adolescents in Germany - Jekauc, Darko; Reimers, Anne Kerstin; Wagner, Matthias; Woll, Alexander (BMC Public Health, 2012)
Background: Regular physical activity (PA) is a prerequisite for normal growth and maturation, health, and fitness of children and adolescents. Because of the growing evidence of the health benefits of regular PA, several national and international public health organisations have established PA guidelines. The purpose of this study was to assess the percentage of children and adolescents in Germany who meet the PA guideline of 60 minutes of moderate-to-vigorous PA each day and to evaluate socio-demographic correlates of compliance with the PA guideline. Methods: The sample consists of 4,529 children and adolescents aged between 4 and 17 years who lived and were registered in the Federal Republic of Germany between 2003 and 2006. The compliance with the PA guideline was assessed using a widely accepted screening measure. Socioeconomic status, immigration background and residential area were assessed using a parent questionnaire. Results: Overall, 13.1% of girls and 17.4% of boys complied with the national guideline of 60 minutes of moderate-to-vigorous PA daily. While compliance was significantly lower in older participants of both gender groups, the steepest decrease in compliance was observed for age groups around the transition time from primary to secondary school. Logistic regression revealed that socioeconomic status and a migration background were significant predictors for compliance in girls and residential area for compliance in boys. Conclusions: Programs and policy action addressing the problem of decreasing compliance with PA guideline with increasing age are warranted. The transition from primary school to secondary school seems to be a critical stage in life with respect to PA behaviour. Therefore, specific interventions should aim at restructuring and reorganising their daily and physical activities during this transition.
Keywords: Physical activity guideline; Socio-demographic; Children; Adolescents; Compliance